A Review of Catalysts for Methylcyclohexane Dehydrogenation - Meng, Junchi; Zhou, Feng; Ma, Huixia; Yuan, Xingzhou; Wang, Yanjuan; Zhang, Jian (Topics in catalysis, 2021)
Methylcyclohexane (MCH) is regarded as an excellent hydrogen energy carrier due to its reasonable theoretical hydrogen storage content (6.22 wt%) and physicochemical performance. Methylcyclohexane-toluene-hydrogen (MTH) cycle realizes the recycling of materials and energy, and has a good prospect of industrial application. The dehydrogenation process is highly reversible, and the industrial hydrogenation process has been commercialized, while the dehydrogenation process of MCH does not exist and the research on the catalytic dehydrogenation of organic liquid hydride is not comprehensive. The development of dehydrogenation catalysts with good stability, catalytic activity and product selectivity under low temperature and high pressure is the central issue of the industrialization of MTH system. In this paper, introducing the advantages of the MTH system and the current research status of MCH catalytic dehydrogenation. Catalysts were classified as active components and summarized from the aspects of carrier selection, preparation methods and dehydrogenation performance, and the research status of noble metal catalyst and non-noble metal catalyst is emphasized. In addition, the research progress of different carrier effect on catalyst performance is briefly reviewed.